From problem-orientedness to goal-orientedness: Re-conceptualizing communication strategies as forms of intra-mental and inter-mental mediation. (October 2016) - Chang, Sin-Yi; Liu, Yongcan
Abstract: The use of communication strategies is one of the core components that constitute communicative competence. However, the problem-oriented conceptualization of L2 strategic behavior has been widely criticized as it does not give sufficient attention to the social nature of communication and learning. This study thus makes an attempt to re-conceptualize communication as a mediated activity that focuses on the process and goal of communication. Eight EFL junior high school learners in Taiwan participated in this study. Empirical data were collected from an oral elicitation task, and then triangulated by retrospective comments derived from stimulated recall interviews and semi-structured interviews with the participants. The data were coded with Dörnyei and Scott's (1995) taxonomy of communication strategies and mapped onto a sociocultural framework of mediation for analysis. The findings showed that the use of strategies was at times problem-oriented for avoiding or solving communication breakdowns. Nevertheless, what seemed more significant was that interlocutors also made efficient choices of strategies according to the context and aim of the task. It is rightly the purpose of this paper to develop an enriched view of L2 strategic competence that acknowledges both the problem-oriented and goal-oriented nature of communication.